Efektivitas Terapi Murotal Surah Ar-Rahman Pada Pasien Tumor Hati Dengan Nyeri Akut Di Ruang Lavender Bawah RSUD Kardinah Tegal - Supriyanto, Azis; Sumarni, Tri (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2025)
Liver tumors are characterized by the abnormal growth of cells in the liver. Acute pain is one of the common symptoms experienced by patients with liver tumors, significantly affecting their quality of life and psychological well-being. Non-pharmacological therapies, such as Qur’anic recitation (murottal), are increasingly used as complementary methods to reduce pain perception. Surah Ar-Rahman is known to produce calming and relaxing effects, both psychologically and physiologically, through its stable sound waves and repetitive recitation rhythm. This study aims to evaluate the effectiveness of Murottal Therapy using Surah Ar-Rahman in reducing pain intensity among patients with liver tumors. The research design is a descriptive case study involving a 44-year-old male patient diagnosed with a liver tumor and undergoing hepatectomy. The intervention involved administering Murottal Therapy with Surah Ar-Rahman for three days (13–15 January 2025). Pain was assessed using the Numeric Rating Scale (NRS) before and after the intervention. The results showed a gradual reduction in pain intensity from a score of 6 (moderate pain) to a score of 2 (mild pain) after three consecutive days of therapy. The significant decrease in pain intensity indicates that Murottal Therapy with Surah Ar-Rahman is effective as a complementary approach to relieve acute pain in liver tumor patients. These findings support the use of Murottal Therapy with Surah Ar-Rahman as a safe and beneficial non-pharmacological intervention in nursing practice. It is recommended that future researchers explore the application of other non-pharmacological therapies for pain management.